Improving Students' Reading Comprehension Achievement by Using Generating Interaction Between Schemata and Text (GIST) Strategy at MTs Al-Hikmah Palembang - Fahira, Bella Anggi; Erlina, Dian; Saputra, Eko (Universitas PGRI Adi Buana Surabaya, 2024)
This research was carried out with the purpose to determine whether there was any significant improvement in students' reading comprehension achievement demonstrated by using GIST strategy at the eighth graders students of MTs Al-Hikmah Palembang and whether there was any significant difference on students' reading comprehension achievement taught by using GIST strategy and lecturing method at the eighth graders students of MTs Al-Hikmah Palembang. This study was conducted at MTs Al-Hikmah Palembang. The researchers employed a true-experimental research method in this study. The researchers selected the sample with the cluster random sampling. This study concentrated on eight-grade students at MTs Al-Hikmah Palembang. In this study, the total sample was 48 students which included experimental and control class. SPSS 25 software was used to analysed the students' pre- and post-test results. From the results, the p-value was .000 with df=23 (2.069) and the t-value was -13.135. Because the p-output was less than 0.05 and the t-output was above the t-table (2.069), it may be assumed that there were significantly higher gains from students' pre-test to post-test scores in the experimental class taught implementing the GIST strategy. On the basis of the results, the p-output was.000 with df=46 (1.916), and the t-output was 4.063. The null hypothesis (Ho) was rejected, while the alternative hypothesis (Ha) was accepted. Because the p-output was less than 0.05 and the t-output exceeded the t-table (1.916). The findings of this study demonstrate that the GIST strategy improved students' reading comprehension achievement in recount text at eighth-grade students of MTs Al-Hikmah Palembang, while there was a significant difference between the experimental and control classes, as demonstrated through the post-test results, with the experimental class better than the control class.